The effectiveness of school-based interventions addressing adolescent mental health in Low- and Middle-Income Countries: A Systematic Review and Meta Analysis - Albertus, Cleo Alyssa (Department of Public Health and Family Medicine, 2020)
Mental health is fundamental to a person's wellbeing and quality of life, as well as, influences social and economic outcomes across an individual's lifespan (Barry, Clarke, Jenkins, & Patel, 2013). The World Health Organization (WHO) defines mental health as a “state of well-being in which an individual realizes his or her own abilities, can cope with the normal stresses of life, can work productively and is able to make a contribution to his or her community” (WHO, 2018). Mental health is considered integral to a person's overall wellbeing and can be determined by a variety of factors such as socioeconomic, environmental and biological (WHO, 2018). Mental health disorders are considered one of the most common causes of disability worldwide, thus resulting in the disease burden of mental illness being an important public health concern (ODPHP, 2019). Mental illness refers to all diagnoseable mental disorders and conditions, which result in significant emotional, social and behavioural changes that cause distress and hamper the individual's ability to function in everyday life (Pareketh, 2018).